2023
DOI: 10.1177/01939459221148825
|View full text |Cite
|
Sign up to set email alerts
|

Health Experiences of Nurses during the COVID-19 Pandemic: A Mixed Methods Study

Abstract: This study characterizes the impact of the COVID-19 pandemic on the mental and physical health of nurses. Qualitative data (collected using semi-structured interviews) were integrated with quantitative data (collected concurrently using the SF-12 Health Survey). Nurses ( N = 30) compared their health prior to and during the first pandemic wave (March–May 2020). Interviews were analyzed thematically; descriptive statistics and t-tests compared pre-pandemic to current SF-12 scores. Qualitative findings demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Similarly, Harris ML et al (2023) revealed that the COVID-19 pandemic had adverse effects on nurses' mental health, including feelings of isolation, loss, strong emotions, and a sense of worthlessness. In addition, they reported physical health problems, including exhaustion and skin problems, due to the prolonged use of personal protective equipment (PPE) [14] . Another study by Vázquez Sánchez MÁ et al (2023) analyzed 25 Spanish nurse interviews to investigate the professional grief experienced by nurses during the COVID-19 pandemic and its impact on nurses' psyche, and consequently on their professional and personal lives.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Similarly, Harris ML et al (2023) revealed that the COVID-19 pandemic had adverse effects on nurses' mental health, including feelings of isolation, loss, strong emotions, and a sense of worthlessness. In addition, they reported physical health problems, including exhaustion and skin problems, due to the prolonged use of personal protective equipment (PPE) [14] . Another study by Vázquez Sánchez MÁ et al (2023) analyzed 25 Spanish nurse interviews to investigate the professional grief experienced by nurses during the COVID-19 pandemic and its impact on nurses' psyche, and consequently on their professional and personal lives.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…During the last couple of years, many studies probed the experience of the first wave of the pandemic through a mixed-method design, collecting both qualitative and quantitative data. Among those studies, those which combined validated questionnaires and open-ended questions or in-depth interviews focused on specific populations, mainly health care workers, nurses and doctors (e.g., Svantesson et al, 2022;Harris et al, 2023;Richards et al, 2023), but also medical students (Rolland, 2022), family caregivers (Leleszi-Tróbert et al, 2022), women with young children (Wandschneider et al, 2022), children with obesity (Welling et al, 2022), supermarket workers (Mayer et al, 2022), and university students (Mourad et al, 2022). To our knowledge, three studies explored the effects of stress during the first wave of the pandemic through a mixed-method design.…”
Section: Introductionmentioning
confidence: 99%
“…example, studies conducted in the United States on the effect of the pandemic on the healthcare workforce have included only small samples of Midwestern healthcare workers, if any, and did not report results by region. 5,8,12,13 Furthermore, within U.S. studies, none found in our recent literature search assessed the mental health of the workforce at multiple time points throughout 2020 and 2021 as waves of COVID-19 cases surged. In addition, limited data have been published on self-care activities in which U.S. healthcare workers are engaged, 3,8,10 and no studies have addressed actions taken by healthcare organizations to support mental wellbeing during the pandemic.…”
mentioning
confidence: 99%